Persepsi Masyarakat Terhadap Naiknya Harga Tiket Kapal Laut Tujuan Batam - Tanjungpinang 2022 - Amalia, Nabilla; Fitani, Keyza Regita; Fajriyah, Latifa Nur (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The rise in BBM prices becomes a global problem, it affects the perception of the people about the rise of the price of ferry tickets to Batam-Tanjungpinang in 2022. The aim of this study is to find out how people see the rise in the price of shipping tickets in Batam-Tanjungpinang in 2022. The research uses descriptive research with a method of qualitative approach. The result of the study is that the public’s perspective on the increase in BBM prices againts the rise in shipping charges is a reasonable thing, because this is a necessity for the people who frequently travel by ships